NDEx: Accessing Network Models and Streamlining Network Biology Workflows. Issue 9 (27th September 2021) - Pillich, Rudolf T.; Chen, Jing; Churas, Christopher; Liu, Sophie; Ono, Keiichiro; Otasek, David; Pratt, Dexter
Abstract: NDEx, the Network Data Exchange (https://www.ndexbio.org ) is a web‐based resource where users can find, store, share and publish network models of any type and size. NDEx is integrated with Cytoscape, the widely used desktop application for network analysis and visualization. NDEx and Cytoscape are the pillars of the Cytoscape Ecosystem, a diverse environment of resources, tools, applications and services for network biology workflows. In this article, we introduce researchers to NDEx and highlight how it can simplify common tasks in network biology workflows as well as streamline publication and access to data. Finally, we show how NDEx can be used programmatically via Python with the 'ndex2' client library, and point readers to additional examples for other popular programming languages such as JavaScript and R. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Getting started with NDEx Basic Protocol 2 : Using NDEx and Cytoscape in a publication‐oriented workflow Basic Protocol 3 : Manipulating networks in NDEx via Python